Development of microbeads of chicken yolk antibodies against Clostridium difficile toxin A for colonic-specific delivery. (23rd July 2016) - Zhang, Shumin; Xing, Pingping; Guo, Guiping; Liu, Hong; Lin, Donghai; Dong, Chuangchuang; Li, Min; Feng, Dongxiao
Abstract: The incidence of Clostridium difficile infection has increased in Western world in the past 10 years, similar infection rates are also reported in developing countries such as China. Current antibiotics treatments have recurrence rates between 15% and 30%. IgY antibodies against toxin A of C. difficile could protect animal models from the challenge of lethal dose of C. difficile spores. However, IgY is sensitive to the low pH environment of the stomach and proteinases in the intestine. The objective of this study was to prepare colonic-specific delivery system of toxin A antigen-specific IgY to block the recognition of toxin A to the colon mucosa cells. Egg-laying hens were immunized with purified C. difficile toxin A C-terminal domain for 3 times, then egg IgY against the recombinant ToxA–C protein was purified from immunized egg yolk and frozen dried. IgY-loaded microbeads were prepared using mini fluid bed system; the loading efficiency was 21%. The pH and temperature stabilities of the microbeads were assayed. The IgY-loaded microbeads coated with 35% Eudragit S100 had colonic-specific IgY release specificity both in vitro and in vivo, the colonic-specific release of biological active IgY was 87.5% in the rat. Our study provides a new option for the biological treatment C. difficile infection.